Analyzing the Use of Augmented Reality in Public Relations Efforts to Improve Tourists' Experience In Ragunan Zoo - Pradini, Gagih; Wardhani, Dwi Kesuma; Awaloedin, Dipa Teruna (International Journal of Education, Information Technology, and Others, 2024)
Augmented Reality (AR) has become an increasingly popular technology across various fields, including tourism. Ragunan Wildlife Park, a zoo in South Jakarta, Indonesia, has introduced an AR application to enhance the visitor experience. This research aims to analyze the use of Augmented Reality in public relations efforts to improve the tourist experience at Ragunan Wildlife Park. Using a descriptive qualitative approach, the study was conducted through on-site observation, in-depth interviews with visitors, and a review of related literature and documentation. Additionally, a SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) was employed to evaluate the impact of AR usage. The study findings indicate that AR in the Ragunan Zoo application adds value by providing additional information about the zoo's fauna and facilities, facilitating online ticket purchases, and reducing wait times. However, AR also faces challenges such as the requirement for a stable internet connection and visitors' lack of familiarity with AR technology. Opportunities arise from the potential to strengthen digital relationships with visitors, while threats include data security risks and visitors' disinterest in using the app. The study concludes that AR has significant potential to enhance the visitor experience at Ragunan Wildlife Park. However, clear guidelines and educational efforts are needed to ensure visitors can easily access and use the application. With straightforward instructions and appropriate promotion, AR can be an effective tool to improve the visitor experience and strengthen the image of Ragunan Wildlife Park.